Co-Evolution in Relation to Small Cars and Sustainability in China: Interactions Between Central and Local Governments, and With Business. (April 2017) - Kolk, Ans; Tsang, Stephen
This article explores how the institutional context, including central and local governments, has co-evolved with business in relation to small cars and sustainability. This issue is very relevant for business and society in view of the environmental implications of the rapidly growing vehicle fleet in China, the economic importance attached to this pillar industry by the government, and citizen interest in owning and driving increasingly larger cars. The interactions between different levels of government, and with business (both domestic and foreign-invested) in countries with a large role for the state is a novel area of study in the business-society area and a complex one given the multitude of objectives and interests involved in industry competitiveness, economic development, energy security, and sustainability. The article shows that the central government has adopted policies to further the production and use of small cars, which it perceives as serving environmental, economic, and social goals. Concurrently, however, many local governments imposed restrictions on small cars and have, implicitly or explicitly, favored larger cars. There seems to be a clear linkage to municipal ownership of those domestic automobile companies which, via joint ventures with foreign firms, focused more on larger cars. By adopting a co-evolutionary approach focused on macro-level interactions, the case helps to shed some more light on concrete sustainability challenges, and broader government–business interactions in a highly institutionalized setting, contributing insights on issues that have remained underexposed in business and society research.